I nationens intresse? En analys av begreppet angeläget allmänt intresse utifrån målet RÅ 1999 ref. 76 - Losjö Dahlström,Alexander (2025)
In 1994 the Swedish constitution was amended to include more protection for the right to property. Among other things, it was written into the consti-tution that expropriation or similar measures was only allowed when it ac-commodated “urgent popular interest” (Swe: “angeläget allmänt intresse”). The updated constitution was widely debated, and the term urgent popular interest was especially controversial. In 1999 Sweden’s Supreme Administrative Court ruled that the state had acted in accordance with the constitution when it decided to close a nuclear power plant, Barsebäck 1. One of the main questions in the ruling was whether an urgent popular interest existed. The ruling too became widely debated and divided experts that were either for or against the ruling. In the ruling’s aftermath, the debate on the term urgent popular interest culminated. This paper examines the interpretation of the term urgent popular interest, as well as how the ruling from the Swedish Supreme Administrative Court regarding Barsebäck 1 stands in relation to the intention of the legislator. To examine this, the paper uses a legal dogmatic study that investigates relevant legal material and analyses and discusses the same. The paper shows that the interpretation of what constitutes an urgent public interest in the end becomes a political question. This is also stipulated by the legislator in preparatory works for the constitution. The paper also argues that the term urgent public interest can be used in a way that ensures that policy which voters have voted for in referendums and other elections can materialize into decisions by the executive government. It is also clear by the legislator’s intent that the term can not be used in a way that is not accepta-ble in a democratic society under rule of law. This gives insurance to indi-viduals that the term does not allow the law to be used arbitrarily.
Keywords: Statsrätt; Regeringsformen; Angeläget allmänt intresse